Synthesis and characterization of fluorescent Carbon quantum dots and their Multifunctional applications - Yadav, Pradeep Kumar (IIT BHU Varanasi, 2022)
Abstract is available in the content
Keywords: Synthesis and characterization of fluorescent Carbon; quantum dots and their Multifunctional applications